Enhanced anti-tumor effect of pH-responsive dextrin nanogels delivering doxorubicin on colorectal cancer - Manchun, S.; Dass, Crispin; Cheewatanakornkool, K.; Sriamornsak, P. (Elsevier Ltd, 2015)
Efficacy of doxorubicin (DOX) in colorectal cancer treatment is limited by undesirable side-effects, which are partially due to nonspecific delivery DOX to the tumor target site. This study aimed to develop pH-responsive dextrin nanogels (DNGs) as anticancer drug carriers with pH-controlled drug release. DNGs prepared with formaldehyde as a cross-linker (FDNGs) exhibited smaller size, compared to that using glyoxal (GDNGs). Both DNGs showed pH-dependent drug release properties; drug release was slow at neutral pH but increased significantly in acidic medium. The cytotoxicity of empty and DOX-loaded FDNGs was lower than free DOX and GDNGs, against two commonly used colorectal cancer cells. Intracellular uptake studies indicated that the DOX-loaded FDNGs could efficiently deliver DOX into the nuclei. In vivo, DOX-loaded FDNGs substantially enhanced anti-tumor efficacy, compared to free DOX, exhibiting much higher effects on inhibiting proliferation and inducing apoptosis, as confirmed by mice weight shifts, tumor weight, tumor volume and histological assessment. Therefore, FDNGs are promising as a potential drug delivery vehicle for colorectal cancer therapy.